Stressogenicity of Media Noise in the Conditions of Background Media Consumption - Andreeva, Yulia Valentinovna; Polianina, Alla Kerimovna (International Journal of Criminology and Sociology, 2021)
The authors of the paper present for the first time the concept of media noise in the living space of modern children; they also introduce the concept of media noise as forced media consumption in a background (backdrop) format, and consumption in parallel with the main activity (foreground). The stressful effect of the operation of screens and players in the background on people in this space, and the impact of the inclusion of children in a continuous media stream are assessed. It is noted that pervasive media increase the potential of psycho-emotional impact through trance methods of exposure affecting the cognitive, affective and behavioural sphere of individuals, and this forces them to consume information, burden the information space of children, and qualitatively change the social situation of their development. The paper presents the findings concerning pilot studies of the media noise phenomenon and the state of media noise. The existence of a relationship between various parameters of forced background media consumption is shown; the main situations of background media consumption, as well as the reasons for the independent media noise initiation and its duration, are given. The aggravated negative impact of background media consumption in connection with the new life realities of mankind during the period of total immersion in the media space is noted; the last is caused by the need for social distance.